Programa educativo “DAMI” para la eficacia de la comprensión lectora en estudiantes del primer grado de secundaria de la Institución Educativa Teniente Manuel Clavero Muga, Iquitos 2022 - Navarro Torres, Damaris Miluska (2025)
The purpose of this study is to analyze the effectiveness of the DAMI program in improving the reading comprehension skills of first-year high school students of the Teniente Manuel Clavero Muga Educational Institution, located in the Punchana district of the city of Iquitos, Maynas province, Loreto region, during the year 2022. It is an evaluative study that assumes a non-equivalent group design. It included 64 students, equally divided into experimental and control groups. To analyze the results, the Mann-Whitney U test was used, which makes it easy to compare two independent groups. The findings of the study indicated that the DAMI program had a notable impact on the development of reading comprehension skills, with a Uc value of 16,000 and a p value of 0.000. Notable progress was made in several areas: literal comprehension reached 108,000 points, showing that students improved in assimilating the topics addressed. In addition, inferential comprehension showed a considerable increase, reaching 160,500 points, indicating that students were able to grasp more complex concepts. Finally, critical comprehension also showed progress, reaching 51,500 points. In conclusion, the DAMI program has been key in facilitating students' understanding and deeper analysis of texts.